Titanium nitride as an electrocatalyst for V(II)/V(III) redox couples in all-vanadium redox flow batteries. (10th November 2015) - Yang, Chunmei; Wang, Haining; Lu, Shanfu; Wu, Chunxiao; Liu, Yiyang; Tan, Qinglong; Liang, Dawei; Xiang, Yan
Abstract: Titanium nitride nanoparticles (TiN NPs) are proposed as a novel catalyst towards the V(II)/V(III) redox pair for the negative electrode in vanadium redox flow batteries (VRFB). Electrochemical properties of TiN NPs were characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The results show that TiN NPs demonstrate better electrochemical activity and reversibility for the processes of V(II)/V(III) redox couples as compared with the graphite NPs. TiN NPs facilitate the charge transfer in the V(II)/V(III) redox reaction. Performance of a VRFB using a TiN NPs coated carbon paper as a negative electrode is much higher than that of a VRFB with a raw carbon paper electrode. The columbic efficiency (CE), the voltage efficiency (VE) and the energy efficiency (EE) of the VRFB single cell at charge-discharge current density of 30 mA/cm 2 are 91.74%, 89.11% and 81.74%, respectively. During a 50 charge-discharge cycles test, the CE values of VRFB with TiN NPs consistently remain higher than 90%.